To find the equivalent expression, we need to put the equation in the form:
![a(x-x_1)(x-x_2)](https://img.qammunity.org/2023/formulas/mathematics/college/jui7os4cjtu6ansvk48v2s1i59wqkga3iq.png)
Where x1 and x2 are the roots of the equation.
So the first step is to find those roots, using the quadratic formula:
![\begin{gathered} -3x^2-24x-36 \\ a=-3,b=-24,c=-36 \\ x_1=(-b+√(b^2-4ac))/(2a)=(24+√(576-4\cdot(-3)\cdot(-36)))/(-6) \\ x_1=(24+√(576-432))/(-6)=(24+√(144))/(-6)=(24+12)/(-6)=(36)/(-6)=-6 \\ x_2=(-b-√(b^2-4ac))/(2a)=(24-√(144))/(-6)=(24-12)/(-6)=(12)/(-6)=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hkkjq1qj5qnttwa247j3ny68f7tp06mri1.png)
So now we have the values of a, x1 and x2, so our equation will be:
![-3x^2-24x-36=-3(x+6)(x+2)=-3(x+2)(x+6)](https://img.qammunity.org/2023/formulas/mathematics/college/3a8otq6kr5nlaz7okw9edqr9os6cwj69ar.png)
So the options to select are -3, 2 and 6.